Inhibitor‐Mediated Structural Transition in a Minimal Amyloid Model. Issue 3 (30th November 2021) - Chakraborty, Priyadarshi; Bera, Santu; Mickel, Phil; Paul, Ashim; Shimon, Linda J. W.; Arnon, Zohar A.; Segal, Daniel; Král, Petr; Gazit, Ehud
Abstract: Despite the fundamental clinical importance of amyloid fibril formation, its mechanism is still enigmatic. Crystallography of minimal amyloid models was a milestone in the understanding of the architecture and biological activities of amyloid fibers. However, the crystal structure of ultimate dipeptide‐based amyloids is not yet reported. Herein, we present the crystal structure of a typical amyloid‐forming minimal dipeptide, Ac‐Phe‐Phe‐NH2 (Ac‐FF‐NH2 ), showing a canonical β‐sheet structure at the atomic level. The simplicity of the structure helped in investigating amyloid‐inhibition using crystallography, never previously reported for larger peptide models. Interestingly, in the presence of an inhibitor, the supramolecular packing of Ac‐FF‐NH2 molecules rearranged into a supramolecular 2‐fold helix (21 helix). This study promotes our understanding of the mechanism of amyloid formation and of the structural transitions that occur during the inhibition process in a most fundamental model. Abstract : The crystal structure of the ultimate dipeptide that forms typical amyloid fibrils shows a canonical β ‐ sheet structure at the atomic level. However, when crystallized in the presence of an amyloid‐inhibitor the supramolecular packing of Ac‐FF‐NH2 molecules rearranged into a supramolecular 2‐fold helix (21 helix).